Bilateral Transcutaneous Electrical Nerve Stimulation Improves Lower‐Limb Motor Function in Subjects With Chronic Stroke: A Randomized Controlled Trial - Kwong, Patrick W. H.; Ng, Gabriel Y. F.; Chung, Raymond C. K.; Ng, Shamay S. M. (Journal of the American Heart Association, 2018)
Background Transcutaneous electrical nerve stimulation (TENS) has been used to augment the efficacy of task‐oriented training (TOT) after stroke. Bilateral intervention approaches have also been shown to be effective in augmenting motor function after stroke. The purpose of this study was to compare the efficacy of bilateral TENS combined with TOT versus unilateral TENS combined with TOT in improving lower‐limb motor function in subjects with chronic stroke. Methods and Results Eighty subjects were randomly assigned to bilateral TENS+TOT or to unilateral TENS+TOT and underwent 20 sessions of training over a 10‐week period. The outcome measures included the maximal strength of the lower‐limb muscles and the results of the Lower Extremity Motor Coordination Test, Berg Balance Scale, Step Test, and Timed Up and Go test. Each participant was assessed at baseline, after 10 and 20 sessions of training and 3 months after the cessation of training. The subjects in the bilateral TENS+TOT group showed greater improvement in paretic ankle dorsiflexion strength (β=1.32; P=0.032) and in the completion time for the Timed Up and Go test (β=−1.54; P=0.004) than those in the unilateral TENS+TOT group. However, there were no significant between‐group differences for other outcome measures. Conclusions The application of bilateral TENS over the common peroneal nerve combined with TOT was superior to the application of unilateral TENS combined with TOT in improving paretic ankle dorsiflexion strength after 10 sessions of training and in improving the completion time for the Timed Up and Go test after 20 sessions of training. Clinical Trial Registration URL: http://www.clinicaltrials.gov. Unique identifier: NCT02152813.